(untitled) (Scientific journal of the Fergana State University, 2023)
Is to reveal the semantic features of the oxymoron phenomenon, to clarify the specific aspects of its classification. Descriptive, synchronic-descriptive, oppositional, comparative, component analysis methods were used to determine the theoretical problems of the oxymoron phenomenon and show its specific features. Scientific views on oxymoron were deeply analyzed, semantic features of unusual combinations were described; functional-semantic means of expression forming the phenomenon of oxymoron were explained; types of semantic relations between oxymoron components were identified. In today’s process of globalization and integration, it is of great importance to further explore the internal capabilities of our national language, which is distinguished by the use of figurative tools in artistic speech, which are considered an integral part of our culture, including syntactic devices formed using the oxymoron method; the main factor that creates oxymoron is the speaker’s boredom with traditional means of expression or his desire to express his own content through a new form and try to draw the recipient’s attention to the speech; oxymorons were classified according to their semantic properties: they create semantic relations such as related to human emotions, characteristics, activities, behavior, physical appearance, age-specific characteristics, natural phenomena, smell-taste, color was studied.